Evaluation of Antioxidant Activity, α-Glucosidase Inhibition, and Malondialdehyde Reduction of Reformulated Galohgor Nutraceuticals from Sundanese-Indonesia - Balgis, Yayik Dwi; Katrin, Roosita; Hadi, Riyadi; Fathimah, Fathimah (Journal of Health and Nutrition Research, 2025)
Galohgor nutraceutical, a traditional herbal formulation from Sundanese-Indonesia, has long been used for its health benefits, including antidiabetic potential. However, studies on α-glucosidase inhibition in its new formulation remain limited. This study aimed to assess the antioxidant activity, α-glucosidase inhibitory potential of the reformulated (F2) of Galohgor Nutraceutical, and its effect on malondialdehyde (MDA) levels. The methods used a completely randomized design (CRD). Antioxidant activity and α-glucosidase inhibitory effect were evaluated using the DPPH (2,2-Diphenyl-1-picrylhydrazyl) method and α-glucosidase inhibition assay. MDA levels were analyzed in vivo using serum samples from mice treated with the reformulated (F2) of Galohgor Nutraceutical. The statistical analysis used was an independent t-test. The results the reformulated (F2) of Galohgor Nutraceutical extract exhibited antioxidant activity, with IC₅₀ values of 2904.06 ppm, while ascorbic acid, used as a positive control, had a significantly lower IC₅₀ value of 8.20 ppm. The α-glucosidase inhibitory activity of the reformulated (F2) extracts showed IC₅₀ values of 30.833,14 ppm, respectively, which were considerably higher than the positive control, acarbose (IC₅₀= 0.16±0.001 ppm). Administrating of the Galohgor extract at a dose of 5000 mg/kg body weight successfull reduced MDA levels. Although not statistically significant (p = 0.131), the observed reduction in MDA levels suggests a protective potential against oxidative stress. The reformulated (F2) of Galohgor Nutraceutical extract has potential as a natural antioxidant and antidiabetic agent